Assessment of subclinical diabetic cardiomyopathy by speckle‐tracking imaging. (4th January 2021) - Minciună, Ioan‐Alexandru; Hilda Orășan, Olga; Minciună, Iulia; Lazar, Andrada‐Luciana; Sitar‐Tăut, Adela Viviana; Oltean, Monica; Tomoaia, Raluca; Puiu, Mihai; Sitar‐Tăut, Dan‐Andrei; Pop, Dana; Cozma, Angela
Abstract: Background: Diastolic dysfunction is traditionally believed to be the first subclinical manifestation of diabetic cardiomyopathy (DCM), leading to systolic dysfunction and then overt heart failure. However, in the last few years, several studies suggested that systolic subclinical dysfunction measured by speckle‐tracking echocardiography (STE) may appear ahead of diastolic dysfunction. In this review, the main endpoint is to show whether subclinical myocardial systolic dysfunction appears ahead of diastolic dysfunction and the implication this may have on the evolution and management of DCM. Materials and methods: We performed a search in PubMed for all relevant publications on the assessment of DCM by STE from 1 June 2015 to 1 June 2020. Results and Conclusions: The results illustrate that subclinical systolic dysfunction assessed by STE is present in early DCM stages, with or without the association of diastolic dysfunction. This could be a promising perspective for the early management of patients with DCM leading to the prevention of the overt form of disease.